ANALISA SAMBARAN PETIR TERHADAP SISTEM PROTEKSI TOWER TELEKOMUNIKASI MENGGUNAKAN SIMULASI SOFTWARE ATP DRAW - Riza Ria Wirasari; Surya Hardi; Rohana Rohana; Muchsin Harahap (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2022)
The increase in the telecommunications network was accompanied by the addition of the number of BTS (Base Transceiver Station) in various regions. The BTS (Base Transceiver Station) tower is built with a minimum height of 25-100 meters. BTS towers are equipped with external and internal grounding protection systems that are designed and installed in accordance with SNI. The protection system is a unified protection system for towers and telecommunications equipment from lightning strikes. Lightning strikes occur randomly which cannot be ascertained and their occurrence is controlled and lightning strikes also cause damage to the object that is struck. ATP Draw is a graphical program from the Electromagnetic Transient Program (EMTP) for Windows. Software Alternating Transient Program (ATP Draw) is used for digital simulation of impulse waves. In this software a lightning protection system is modeled in the form of an electrical circuit, and a lightning impulse waveform against a lightning protection system circuit. analyzed the lightning protection system on the BTS tower by performing simulations using ATP Draw software with a power line model with Standard IEC 1.2 x 50 s showing the simulation results of a lightning surge current of 30389 A. for a lightning surge input current of 80 kA, 36088 A for a lightning current input lightning surge of 95 kA, and 37987 A for lightning surge input current of 100 kA. For modeling the standard CIGRE 3.3x77.5μs power line, the simulation results for a lightning surge current of 40644 A for a lightning surge input current of 80 kA, 48264 A for a lightning surge input current of 95 kA, and 50805 A for a lightning surge input current of 100 kA.